Green hydrogen potential in tropical countries: The colombian case - Rodríguez-Fontalvo, David; Quiroga, Eliana; Cantillo, Nelly M.; Sánchez, Néstor; Figueredo, Manuel; Cobo, Martha (International journal of hydrogen energy, 2024)
Tropical countries can approach their natural resources to produce low-carbon H2 from solar, wind, hydro, and biomass resources to satisfy their domestic demand and to export it. To do so, Colombia published the National Hydrogen Roadmap, in which green H2 was prioritized. This study estimates Colombia's potential to produce green H2 and a timeline of scenarios displaying the required installed capacity, capital investment, and environmental analysis related to water utilization and CO2 capture. Accordingly, Colombia can produce H2 at a rate of 9 Mt/a by 2050 by installing 121 GW renewables while processing 303 Mt/a of residual biomass. In this scenario, Colombia's share of the H2 international market can reach 1.2%, with a cumulative investment of over 244 billion USD by 2050. This study provides insights into potential global resources for low-carbon H2 generation. [Display omitted] •Colombia's National Hydrogen Roadmap expects a H2 demand of 1.9 Mt/a by 2050.•Green H2 production potential for Colombia was assessed in 5 scenarios.•Potential of solar, wind, and biomass -based energy sources were studied.•Up to 9 Mt/a of H2 can be produced in 2050 by combining these technologies.•Over 244 billion USD was estimated to be needed as total investment for this scenario.